Turmeric : The Genus Curcuma - Ravindran, P N; Ed. Sivaraman, K; Ed (CRC Press, 2007)
Turmeric's largest producer and exporter, this book explore the history, biotechnology, production, chemical constituents, market trends, processing and medical uses of this versatile herb. Providing a complete industrial profile, it details the spice's sources, as well as export/import data.